2005
DOI: 10.1021/bi0476329
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Formation of the Pyrrole Moiety during Clorobiocin and Coumermycin A1 Biosynthesis

Abstract: The aminocoumarin antibiotics clorobiocin and coumermycin A(1) target the B subunit of DNA gyrase by presentation of the 5-methyl-pyrrolyl-2-carboxy ester moiety in the ATP-binding site of the enzyme. The pyrrolyl pharmacophore is derived by a four electron oxidation of a prolyl unit while tethered in phosphopantetheinyl thioester linkage to a peptidyl carrier protein (PCP) subunit. l-Proline is selected and activated as l-prolyl-AMP by adenylation domain enzymes (CloN4 and CouN4) and then installed as the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 27 publications
7
111
0
Order By: Relevance
“…Of these, only ␣-ketopyrrole moieties are found in a wide variety of biologically active natural products. Feeding experiments have shown that the ␣-ketopyrrole of calcimycin is derived from L-proline (11,33). Biosynthesis of Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, only ␣-ketopyrrole moieties are found in a wide variety of biologically active natural products. Feeding experiments have shown that the ␣-ketopyrrole of calcimycin is derived from L-proline (11,33). Biosynthesis of Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In analogy to the requirement of CoA thioester-bound substrates for C ␣ -H acidification in fatty acid dehydrogenation (21), abstraction of the ␣-proton from ␦-chloro-(allo-)Ile-S-KtzC could be facilitated by the phosphopantetheinyl thioester, to be followed by a removal of ␤-hydride. Similar flavoprotein dehydrogenases catalyze ␣,␤-dehydrogenation of T domain-bound thioesters in the biosynthesis of pyrrole moieties in pyoluteorin and undecylprodigiosin (22,23). Analogous dehydrogenation of ␦-chloro-(allo-)Ile-S-KtzC would yield an enamine intermediate, where C ␤ could serve as an intramolecular nucleophile in cyclopropane formation.…”
Section: Resultsmentioning
confidence: 99%
“…Here we describe a mass spectrometry based method to identify substrates based on mass changes that take place during acylation of a phosphopantetheinyl functionality on the carrier domain(s) of an NRPS protein from very complex substrate reaction mixtures. Observing such acylations by mass spectrometry on carrier domains is now becoming routine (5,19,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).The general method to identify covalently loaded substrates or intermediates is shown in Figure 1. Overproduced protein that contains a carrier domain is purified and incubated with Sfp, a promiscuous phosphopantetheinyl transferase from B .subtilis, and CoA in order to generate the holo form of the carrier domain (37).…”
mentioning
confidence: 99%
“…Therefore we wanted to develop an alternative method for substrate screening to complement the more traditional radioactive assays (5,6). In NRPS and PKS systems, the substrates and intermediates are loaded onto and processed while attached to the pantetheinyl functionality on a carrier domain (7,8).…”
mentioning
confidence: 99%